2008
DOI: 10.1002/cb.248
|View full text |Cite
|
Sign up to set email alerts
|

Market mavenism and consumer self‐confidence

Abstract: The purpose of this study was to test hypothesized associations between market mavenism and consumer self-confidence (CSC). A survey of 190 US consumers provided the data. The results showed significant relationships between mavenism and several dimensions of CSC, and regression analysis emphasized the relationships with two of these: information acquisition (confidence in the ability to obtain and use marketplace information) and social outcomes decision making (confidence in obtaining positive reactions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 15 publications
5
77
0
4
Order By: Relevance
“…Some studies find mavens are more likely to be female (Goldsmith et al, 2006;Kontos et al, 2011;Williams & Slama, 1995), and others found a tendency for mavens to be of lower socio-economic groups . Overall, however, from a socio-demographic profiling perspective the market maven remains elusive (Clark, Goldsmith, & Goldsmith, 2008;Walsh et al, 2004;Wiedmann et al, 2001). There is no theoretical reason why boomer mavens should have a different socio-demographic profile than those belonging to younger cohorts, thus it is suggested that:…”
Section: Socio-demographicsmentioning
confidence: 99%
“…Some studies find mavens are more likely to be female (Goldsmith et al, 2006;Kontos et al, 2011;Williams & Slama, 1995), and others found a tendency for mavens to be of lower socio-economic groups . Overall, however, from a socio-demographic profiling perspective the market maven remains elusive (Clark, Goldsmith, & Goldsmith, 2008;Walsh et al, 2004;Wiedmann et al, 2001). There is no theoretical reason why boomer mavens should have a different socio-demographic profile than those belonging to younger cohorts, thus it is suggested that:…”
Section: Socio-demographicsmentioning
confidence: 99%
“…Literature confirms that self-confident consumers would be selective, yet focussed in their information search Clark et al, 2008;Bishop and Barber, 2012) because they either already possess the product knowledge, or know where to find and access the information they require. They also know how to evaluate product alternatives and how to reduce risk (Loibl et al, 2009;Bishop and Barber, 2012), which fuels the assumption that selfconfident consumers possess persuasion knowledge.…”
Section: Self-confidence During Consumer Decision-makingmentioning
confidence: 99%
“…One view is that CSCencompasses an individual's relative stable self-appraisal that is grounded in a person's self-concept, proposing that CSCis based on a subjective evaluation of one's confidence in your own abilities and authority to act in a specific context in the market place (Adelman, 1987;Blascovich & Tomaka, 1991;Clark et al, 2008;Moorman et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They initiate discussions with consumers and respond to requests from consumers for market information (Feick and Price 1987). Market mavens are confident about their ability to acquire information and to choose between alternative products (Clark 2008). All of these definitions indirectly stipulated that the most salient hallmark of market mavens is their possession of a wide range of market place information.…”
Section: Knowledge Level Of Market Mavensmentioning
confidence: 99%